How Far AI Should Go: A Discourse Analysis of the AI-Attributed Ownership in Filipino Online Discourse on Ghiblified Art - Gallo, Angelika Shen D.; Galdiano, Ritchelle I.; Aperocho, Maico Demi B. (Future Science / FSH-PH Publications, 2025)
The Studio Ghibli AI trend, an online phenomenon that has sparked a widespread fascination amongst individuals, swept across social media platforms after gaining significant traction on March 26. Grant Slatton, a software engineer later branded as the trendsetter, posted an AI-generated image of him and his wife along with their dog at the beach, rendered in the signature style of Studio Ghibli. The researchers noticed that many scholars have conducted similar research about the use of AI in Ghibli-style art; however, the research results are lacking, and more findings are needed to understand the topic thoroughly. The main objective of this study is to identify the dominant discourse used by the netizens present during the online discussion. Identifying the dominant discourse use will help the researchers understand why netizens use this discourse to gain power through language use. This research will analyse the dominant discourse use found in the comment section, specifically, it analyzes the prevailing discourse patterns in the social media discussion using Harris's (1952) framework; these dominant discourses were analyzed to examine how it is being used to establish power through language use in the comment section. The findings reveal that the dominant discourse presented in the corpora includes: